Fechamento da porosidade central na laminação de fio-máquina - Andre Luiz Assuncao (2007)
It was studied in this work the influence of deformation temperature, rolling speed and reduction of area in the closure of an artificial central longitudinal porosity, in rectangular cross section specimen for flat rolling in laboratory, and billets for wire rod rolling. Design of Experiment (DOE) was performed to know the best condition to the closure of the central porosity. For flat rolling at the DEMET/UFMG laboratory, a DOE wascarried out testing 4 parameters (temperature, rolling speed, reduction of area and steel grade) in two levels, and for wire rod rolling it was carried out a DOE testing 3 parameters (temperature, rolling speed and reduction of area) in 2 levels. After rolling, samples were cut out on cross section, polished and etched to identify the remaining central porosity by optical microscopy. The area of the central porosity was measured, and the effectiveness of the closure was checked by a regression analysis.The results for flat rolling have shown the influence of temperature, speed rolling and reduction of area in the closure of the central porosity by flat rolling, and the best condition was in high temperature, low speed and high reduction, and it was more effective in low carbon steel than in alloy steel at the same conditions. For wire rod rolling the results have shown the interaction of the same parameters above, and the best condition was in high temperature, low speed and low reduction of area in the ovalgroove rolls (higher D/h0 ratio in the round grooves).